2013
DOI: 10.1002/ajmg.a.36294
|View full text |Cite
|
Sign up to set email alerts
|

Surgical intervention for esophageal atresia in patients with trisomy 18

Abstract: Trisomy 18 is a common chromosomal aberration syndrome involving growth impairment, various malformations, poor prognosis, and severe developmental delay in survivors. Although esophageal atresia (EA) with tracheoesophageal fistula (TEF) is a potentially fatal complication that can only be rescued through surgical correction, no reports have addressed the efficacy of surgical intervention for EA in patients with trisomy 18. We reviewed detailed clinical information of 24 patients with trisomy 18 and EA who wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 24 publications
2
26
0
Order By: Relevance
“…Although palliative care had been adopted for trisomy 18 patients, there have recently been reports on intensive treatment, including invasive procedures, for infants with trisomy 18 (Graham et al 2004;Kosho et al 2006Kosho et al , 2013Kaneko et al 2008Kaneko et al , 2009Iwami et al 2011;Maeda et al 2011;Nishi et al 2013). Iwami et al (2011) reported that the survival rate and the infants who were able to be discharged home increased significantly after intensive treatments, such as surgical operations for heart disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although palliative care had been adopted for trisomy 18 patients, there have recently been reports on intensive treatment, including invasive procedures, for infants with trisomy 18 (Graham et al 2004;Kosho et al 2006Kosho et al , 2013Kaneko et al 2008Kaneko et al , 2009Iwami et al 2011;Maeda et al 2011;Nishi et al 2013). Iwami et al (2011) reported that the survival rate and the infants who were able to be discharged home increased significantly after intensive treatments, such as surgical operations for heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the mortality rate, withholding or withdrawal of intensive treatment (cesarean-section (C-section) for fetal indication, resuscitation, respiratory support and surgery) had been considered and palliative care had been recommended to the parents (Carter et al 1985;Bos et al 1992;Embleton et al 1996). Recently, some reports have been published about the intensive care and the surgical procedures for infants with trisomy 18, concluding that intensive care and surgical procedures could improve the prognosis of infants with trisomy 18 (Graham et al 2004;Kosho 2008;Kosho et al 2006Kosho et al , 2013Kaneko et al 2008Kaneko et al , 2009Iwami et al 2011;Maeda et al 2011;Nishi et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…We evaluated 24 children with full T13 (15 boys, 9 girls), who were admitted to Nagano Children's Hospital from 1994 to 2016. Children with T18 or T13 were managed under the principle of providing standard intensive neonatal and pediatric treatment through careful discussion with the parents based on evidence from previous literature (Kosho et al, ; Nishi et al, ). Management comprised resuscitation (e.g., intratracheal intubation), appropriate respiratory support, establishment of enteral nutrition (e.g., corrective and palliative surgery for gastrointestinal malformations), and pharmacological treatment for infection, seizures, and congenital heart defects.…”
Section: Methodsmentioning
confidence: 99%
“…Although cardiac surgery has been suggested to be efficient (Graham et al, ; Kaneko et al, ; Maeda et al, ), the efficacy of intensive neonatal and pediatric management without cardiac surgery has not been described. Previously, we demonstrated efficacy of intensive neonatal treatment without cardiac surgery (Kosho et al, ) and surgery for esophageal atresia (Nishi et al, ) on survival of children with T18 from experiences in Nagano Children's Hospital. This hospital is a tertiary prefectural hospital for sick children in Japan, where intensive neonatal and pediatric management without cardiac surgery is routinely provided to children with T18 or 13.…”
Section: Introductionmentioning
confidence: 99%
“…In such syndromes, with poor long-term survival, surgical treatment of associated EA may be seen as cause of unjustified, prolonged suffering to the infant and a waste of the scarce medical resources. A recent report 37 describes the results of surgical treatment of EA in 24 patients with Edwards syndrome. The authors performed palliative surgery in 9 patients (gastrostomy or jejunostomy with/without TEF ligation) and complete repair (primary or delayed) in 15 patients.…”
Section: General Patients' Characteristicsmentioning
confidence: 99%